Overexpression of pyrophosphatase leads to increased sucrose degradation and starch synthesis, increased activities of enzymes for sucrose-starch interconversions, and increased levels of nucleotides in growing potato tubers - Sonnewald, Uwe; et al. (Planta, 1998)
Overexpression of inorganic pyrophosphatase (PPase) from Escherichia coli in the cytosol of plants (ppal plants) leads to a decrease of inorganic pyrophosphate (PPi; U. Sonnewald, 1992, Plant J 2. 571-581). The consequences for sucrose-starch interconversions have now been studied in growing potato (Solanum tuberosum L. cv. Desiree) tubers. Sucrose is degraded via sucrose synthase and UDP-glucose pyrophosphorylase in growing tubers, and it was expected that the low PPi in the ppal transformants would restrict the mobilisation of sucrose and conversion to starch. Over-expression of PPase resulted in an accumulation of sucrose and UDP-glucose, and decreased concentrations of hexose phosphates and glycerate-3-phosphate in growing ppal tubers. Unexpectedly, the rate of degradation of [C-14] sucrose was increased by up to 30%, the rate of starch synthesis was increased, and the starch content was increased by 20-30% in ppal tubers compared to wildtype tubers. Reasons for this unexpectedly efficient conversion of sucrose to starch in the ppal tubers were investigated. (i)The transformed tubers contained increased activities of several enzymes required for sucrose-starch interconversions including two- to threefold more sucrose synthase and 60% more ADP-glucose pyrophosphorylase. They also contained 30-100% increased activities of several glycolytic enzymes and amylase, increased protein, and unaltered or slightly decreased starch phosphorylase, acid invertase and mannosidase. (ii) The transformants contained higher pools of uridine nucleotides. As a result, although the UDP-glucose pool is increased two- to threefold, this does not lead to a decrease of UTP or UDP. (iii) The transformants contained twofold larger pools of ATP and ADP, and ADP-glucose was increased by up to threefold. In stored ppal tubers, there were no changes in the activities of glycolytic enzymes, and nucleotides did not increase. It is concluded that in growing tubers PPi has a wider significance than just being an energy donor for specific reactions in the cytosol. Increased rates of PPi hydrolysis also affect general aspects of cell activity including the levels of nucleotides and protein. Possible ways in which PPi hydrolysis could affect these processes are discussed.
Keywords: nucleotide; pyrophosphatase; Solanum (carbohydrate metabolism); starch; sucrose; tuber